PENGARUH LINGKUNGAN TEMAN SEBAYA TERHADAP PERILAKU SOSIAL ANAK USIA 5-6 TAHUN - Utami, Dian Tri (UIR PRESS, 2018)
The child spends a lot of time interacting in the outer environment with peers in various activities. They showed symptoms of sharing tasks, competition, contention, sympathy, slings help in facing difficulties. This picture shows symptoms of social behavior, there is a good social behavior and social behavior is not good. The purpose of this study is to determine the influence of peer environment on the social behavior of children aged 5-6 years in Kindergarten Humairoh Kubang Jaya Village Siak Hulu District Kampar Regency. This research uses the form of quantitative research with correlational approach. Data collection techniques used in this study is observation. This study uses statistical analysis in the form of chi-square method. The results showed that the peer environment has a strong influence on the social behavior of children. This can be seen from the average score of social and environmental behavior of peers obtained in good category (77.55%) and (74.42%). From the result of the research, it is found that the value of χ² = 19.54 and χ²table = 9.49 so that χ²count ≥ χ²table or 19.54 ≥ 9,49 thus the null hypothesis (Ho) is rejected, that is there is a significant influence from peer environment to social behavior of children aged 5-6 years in Kindergarten Humairoh Kubang Jaya Village Siak Hulu District Kampar District. The effect of variable X to Y is 57%.